Intervensi Berbasis Mindfulness untuk Menurunkan Stres pada Orang Tua - Rahmantika Kurnia Romadhani; M. Noor Rochman Hadjam (Faculty of Psychology, Universitas Gadjah Mada, 2017)
The purpose of this research is to reduce parents’ stress by increasing their mindfulness ability using Mindfulness intervention. Participants in this study consisted of 15 mothers with stress from mild to severe. The design used in this study is quasi-experimental design with an untreated control group with pretest and posttest. The program consists of 8 session intervention. The instruments used in this research are DASS Scale and KIMS scale. The quantitative analysis was conducted through a statistical test using Mann-Whitney and also qualitative analysis. The result of this study showed that intervention with mindfulness was effective to reduce stress in parents (U=0,000; p<0,001).